The effectiveness of mHealth interventions on postpartum depression: A systematic review and meta-analysis. (February 2022) - Zhou, Chuqing; Hu, Hua; Wang, Chunyi; Zhu, Ziyu; Feng, Gengchen; Xue, Jingping; Yang, Ziyi
Introduction: Postpartum depression (PPD) is a common psychiatric condition during the postnatal period that negatively impacts the well-being of both the mother and her infant. This study describes a systematic review and preliminary meta-analysis to assess the efficacy of mobile health (mHealth) interventions, which is defined as the use of portable electronic devices to support public health and medical practice, in addressing depressive symptoms among postpartum women. Methods: Databases including PubMed, PsycINFO, the Cochrane Library, Embase and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) assessing the effectiveness of mHealth interventions on PPD from database inception to December 2019. Results: The initial search identified 754 studies, of which, 11 studies fulfilled the inclusion criteria. These studies evaluated four types of distinct mHealth interventions and involved 2424 participants across six countries. Pooled results demonstrated that compared to the controls, the Edinburgh Postnatal Depression Scale score decreased in the mHealth intervention group (mean difference: –1.09, 95% confidence interval: –1.39 to –0.79). Discussion: Our study suggested that mHealth interventions may be a promising tool to complement routine clinical care in the prevention and treatment of PPD, but the clinical effectiveness of mHealth interventions needs to be better established. While most studies focused on telephone-based interventions, recent researches have also suggested the superiority and effectiveness of short messaging service (SMS) and smartphone applications, but the exact efficacy needs further evaluation. Therefore, more high-quality RCTs on app-based and SMS-based interventions are needed before the large-scale roll-out of these interventions in clinical practice.